Silvopastoral use of Nothofagus antarctica forests in Patagonia: impact on soil microorganisms - Gargaglione, Veronica Beatriz; Gonzalez-Polo, Marina; Birgi, Jorge Alberto; Toledo, Santiago; Peri, Pablo Luis (Springer, 2023)
Soil microorganisms contribute to soil carbon storage, soil respiration and nutrient cycling. In south Patagonia, there are scarce studies on carbon (C) and nitrogen (N) in soil microbial biomass (MB). The aim of this work was to evaluate C and N content in soil MB, and soil microbial respiration according to different sites and forest uses: Nothofagus antarctica primary forests (PF), silvopastoral forests (SPF) and open site (OS). For MB determination, soil samples (0–10 cm depth) were collected in spring (November) and summer (February) over two years. Soil microbial biomass C (SMB-C) was determined using the chloroform fumigation-extraction method and soil microbial biomass N (SMB-N) by a modification of the fumigation–incubation method. Significant differences were observed in SMB-C according to site, forest use and year. Morro Chico ranch presented the lowest SMB-C (721.4 µg C g−1) whereas Tres Marías had the highest (1216.6 µg C g−1). For forest use, the gradient PF >SPF > OS was observed. SMB-N also presented differences and SPF had significantly lower SMB-N (110.9 µg N g−1 soil) than PF (137.5 µg N g−1 soil) and OS (141.76 µg N g−1 soil). The total cumulative respiration was 9657, 10,560 and 12,780 mg C kg−1 for SPF, OS and PF, respectively. Our results support the hypothesis that silvopastoral use of N. antarctica forests affects SMBC. This should be considered if N. antarctica trees are going to be remove to install silvopastoral systems, because this clearly affects soil microorganisms, and in consequence, soil carbon dynamics.